Impact of pre-procedural dual antiplatelet therapy on periprocedural myocardial infarction in patients undergoing percutaneous coronary interventions with adjunctive tirofiban. Issue 164 (April 2018) - Verdoia, Monica; Pergolini, Patrizia; Barbieri, Lucia; Rolla, Roberta; Nardin, Matteo; Negro, Federica; Suryapranata, Harry; De Luca, Giuseppe; ,
Abstract: Background: Recent trials have failed to demonstrate any clinical benefit from pre-treatment with dual antiplatelet therapy (DAPT) in patients undergoing percutaneous coronary interventions, (PCI), even in the setting of acute coronary syndrome. However, suboptimal platelet inhibition during (PCI) has been shown to enhance the risk of acute ischemic complications, such as stent thrombosis and periprocedural myocardial infarction (PMI), thus raising the attention on the potential advantages of adjunctive glycoprotein IIbIIIa inhibitors to obviate to the delayed onset of action of oral antiplatelet drugs. The aim of the present study was then to evaluate the impact of platelet reactivity and pre-procedural DAPT on PMI in patients undergoing PCI with adjunctive tirofiban. Methods: In a consecutive cohort of patients undergoing PCI with tirofiban (intracoronary/intravenous ± prolonged infusion), periprocedural myonecrosis was defined as troponin I increase by 3 times the ULN or by 50% of an elevated baseline value, whereas PMI as CKMB increase by 3 times the ULN or 50% of baseline. Platelet function was assessed by impedance aggregometry. Results: A total of 168 patients were included, 77 (45.8%) of whom were on DAPT at the time of PCI. Patients on DAPT had more often a history of previous PCI ( p = 0.03), higher ACS at admission ( p < 0.001) and creatinine levels ( p = 0.03). Coronary calcifications and type C lesions were more frequent in patients without DAPT ( p = 0.02 and p = 0.03, respectively), as much as TIMI flow < 3 ( p = 0.03), while procedural characteristics were comparable. Baseline platelet reactivity was significantly reduced in DAPT treated patients ( p < 0.001 for ASPI, COL and ADP tests). However the rate of periprocedural myonecrosis did not differ according to pre-procedural DAPT (68.4%vs 67%, p = 0.87; adjusted OR[95%CI] = 1.34[0.71–2.53], p = 0.36) and neither the occurrence of PMI (13.3% vs 12.6%, p = 0.99; adjusted OR[95%CI] = 1.24[0.51–3.1], p = 0.64). Furthermore, baseline platelet reactivity was similar in patients with and without PMI/myonecrosis with no relationship between platelet function and Troponin I peak. Conclusion: In patients undergoing PCI with adjunctive GP IIb-IIIa inhibitors, preprocedural DAPT and baseline platelet reactivity are not associated to the risk of periprocedural myocardial infarction or myonecrosis. These data further support the role of periprocedural Gp IIb-IIIa inhibitors in order to overcome any suboptimal inhibition of platelet aggregation at the time of the procedure due to drug-resistance or delayed (downstream) administration of ADP antagonists, especially in complex high-risk procedures.